Selection of suitable areas for landfill installation in a Brazilian municipality through free software spatial analysis - Bertani Dall'Agnol, Ana Luiza; Nazari, Mateus Torres; Demarco, Carolina Faccio; Afonso, Thays França; Caballero, Cassia Brocca; Hoss, Louise; Leandro, Diuliana; Andreazza, Robson; Quadro, Maurizio Silveira (Ciência e Natura, 2019)
Municipal solid waste (MSW) increasing generation is related to population growth and higher consumption patterns. MSW management is still considered an issue for Brazilian municipalities due to its high complexity, specificity and amount. Landfills are considered a suitable method for final disposal of solid waste, being the technique used in Brazil. Among numerous applications, Geographic Information Systems (GIS) have been widely applied to select sites for landfills implementation. To meet regulatory requirements, choosing a landfill site requires several studies that consume time and resources. The aim of this work was to identify, through the use of GIS, areas that met regulatory and normative standards to landfill installation in a medium sized Brazilian city. It was possible to select three appropriate areas for the location of a landfill in the studied municipality. Considering the need for municipalities to comply with legislation, which demands the elimination of waste disposal in dumps and controlled landfills, properly designed and localized landfills are essential to the Brazilian reality in terms of MSW integrated management. The GIS is evidenced as an effective tool, since it reduces the number of field surveys, optimizing time and reducing economic and human resources needs for the landfill project preparation phase